Serum levels of Heat Shock Protein-70 in Patients with Oral Lichen Planus - Albanidou-Farmaki E.; Andreadis D.; Poulopoulos A.; Farmakis K.; Markopoulos A. (Balkan Stomatological Society, 2014)
Usually increased presence of Heat Shock Proteins (HSPs) is considered to mediate inflammation process in Oral Lichen Planus (OLP) lesions, but in contrast HSP-70 expression found to be stable or even decreased in those lesions. The purpose of this study was to detect the serum titres of the HSP-70 in patients with OLP compared to healthy individuals, which may indicate an alternative, systemic role. Serum levels of HSP-70 were detected by sandwich-ELISA in 45 patients with reticular (n=28) and erosive (n=17) OLP, respectively. A group of 35 healthy individuals was used as control. HSP-70 was detected in significantly increased levels in OLP (p<0.05) compared to controls. The increase was prominent in reticular-OLP (p<0.05), whereas no difference was observed between serum HSP-70 in erosive OLP compared to controls. These results indicate a systemic initiation of the immune response in the pathogenesis and process of OLP. The higher titres of HSP-70 in reticular but not erosive form of OLP indicate rather an immunoregulatory role in chronicity than in the acute inflammatory process of OLP. Consequently, the evaluation of serum imbalances of HSP-70 in OLP using ELISA may be a useful marker for disease's monitoring and/or efficacy of systemic treatment.